Integrated Analysis of Network and Protection System in future Grids - Fuchs, Jochen; Jäger, Johann (IEEE AFRICON, 2013)
The paper presents a robust protection assessment system for integrated analysis of network and protection systems. Especially in future networks with varying and hardly predictable conditions, protection targets as dependability, security and speed are increasingly violated. Protection maloperation leading to unwanted supply interruptions are the consequences. The proposed system is preferred for assessment of smart grids, but other networks can be assessed as well. Analysis of network, including all network's operational states and relay installation points, is essential. Protection system responses are derived from simulation results. Assessment of protection is focused on dependability, security and speed of protection systems and its impact on economic aspects. Due to design of algorithms and parallel computing techniques, the invented system is capable to handle complex structures of large distribution or transportation networks under various conditions. The system detects serious bottlenecks in the protection system behavior and derives indications for improvement. The prospective knowledge of those hidden failures gives the opportunity to reduce the risk of unnecessary disturbances or blackout
Keywords: Integrated analysis; smart grid; protection assessment; dependability; security